JA:2021-21. Improving Safety and Health in the Cattle Feedyard Industry. Issue 3 (2nd July 2020) - Oatman, Jill; Ramos, Athena; Keenan, Mike; Yoder, Aaron
ABSTRACT: Introduction : In 2014, the occupational fatality rate was 116 fatalities/100, 000 workers in the beef cattle ranching and farming industries (including feedyards). This rate was four times higher than the rate in the agriculture, forestry, and ﬁshing sector overall (24.9/100, 000) and 34 times higher than the rate in all industries combined (3.4/100, 000). The cattle feedyard subsector also has exceptionally high non-fatal injury and illness rates. In 2013, hired workers in the beef cattle ranching and farming (including feedyards) had a "days away from work" rate of 258.8/10, 000, while the rate for all industries combined was 99.9/10, 000. The Central States Center for Agricultural Safety and Health (CS-CASH) is ideally located to conduct such research, as half of the feedyards in the United States are located in the Center's region. Purpose : The propose of this project is to reduce the burden of injuries and illnesses among feedyard workers by developing, implementing, and evaluating a comprehensive feedyard safety and health training program. Methods (if applicable ): The Specific Aims of this project are to develop and implement a comprehensive feedyard safety and health training program and evaluate the efficacy of the comprehensive feedyard safety and health training program. Results/Findings : This project is research in progress. A portion of the comprehensive feedyard safety and health training program, known as the Feedyard 15, have been created, and trainings with the Feedyard 15 materials have begun at several feedyards in the CS-CASH region. Practical Application : This project is developing high-quality safety and health materials through a consensus process that involves stakeholders from the feedyard industry. Once tested in a subset of the industry, they will be available industry wide.